Job attitudes in management: perceived satisfaction and importance of needs
Journal of applied psychology. Vol. 46, 1962, no. 6, Dec., p. 375-384; vol. 47, 1963, no. 2, p. 141-148, no. 4, p. 267-275, and no. 6, p. 386-397. Institute of Industrial Relations. Repr. no. 229 (series 6: Industrial psychology and sociology), 1964.